2008
DOI: 10.1159/000156999
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus and Vestibular Schwannomas: Considerations about the Impact of Gamma Knife Radiosurgery

Abstract: Hydrocephalus may occur at various stages of the natural course of vestibular schwannoma and can also be diagnosed after the therapeutic procedure. The aim of the present study was to analyze the impact of Gamma Knife radiosurgery (GKR) on previously diagnosed hydrocephalus (group A patients) and to evaluate the incidence of de novo hydrocephalus after GKR (group B patients). We reviewed retrospectively our case material and the data from the literature. Among the first 1,000 vestibular schwannoma patients tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…It has been reported that both gamma knife radiosurgery and microsurgery can contribute to the development or aggravation of hydrocephalus (Fukuda et al, 2007;Roche et al, 2008). However, the mechanism that is associated with the development of hydrocephalus following gamma knife radiosurgery is not known.…”
Section: Discussion Regarding the Development Of Hydrocephalus In Patmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that both gamma knife radiosurgery and microsurgery can contribute to the development or aggravation of hydrocephalus (Fukuda et al, 2007;Roche et al, 2008). However, the mechanism that is associated with the development of hydrocephalus following gamma knife radiosurgery is not known.…”
Section: Discussion Regarding the Development Of Hydrocephalus In Patmentioning
confidence: 99%
“…Several authors have reported treatment strategies for hydrocephalus before microsurgery or gamma knife radiosurgery (Atlas, et al, 1996;Fukuda, et al, 2007;Roche, et al, 2008). With respect to microsurgery, several investigators preferred a wait-and-see-approach and therefore focused only on the surgery for the tumour.…”
Section: Discussion Regarding the Development Of Hydrocephalus In Patmentioning
confidence: 99%
“…1,2 Although it has been reported that gamma knife radiosurgery may contribute to the development of hydrocephalus, a causal relationship has not been established and remains controversial. [1][2][3][4][5][6][7] The time course of events in this case suggests a contributory role of gamma knife treatment in the development or exacerbation of hydrocephalus. Indeed, in the few reported cases in which a time line is documented, the time course of events is similar, with hydrocephalus developing 4 to 18 months after radiosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a high correlation between the presence of hydrocephalus and the size of schwannoma, the concentration of CSF proteins and the duration of disease [6] [9] [10]. They reveal that a prolonged duration of the disease and a high level of protein in the CSF secondary to the presence of the tumor in elderly patients contribute to the formation of communicating hydrocephalus [11].…”
Section: Age Sex and Location Of Schwannomamentioning
confidence: 99%
“…The presence of schwannoma outside the blood-brain barrier allows blood proteins to pass through the cleft and interendothelial junctions of the tumor to the surrounding CSF [12]. Communicating hydrocephalus is thought to be predominant in older SV carriers [10] [16]. We will simply say that the presence of the neuroma is a predisposing factor to hydrocephalus whatever the age.…”
Section: Hydrocephalusmentioning
confidence: 99%